Comprehensive Assessment of Soil Chemical and Physical Properties across India - Renshu,; Meenakshi,; Sonia,; Juneja, Poonam (Chemical and Materials Sciences: Research Findings Vol. 1, 2025)
Agriculture is considered as the backbone of Indian Society. A nutritious diet is essential for leading a quality lifestyle and it is derived from agricultural fields. We should prioritize and preserve the quality of our soil. This chapter will promote knowledge on the research of various aspects of soil and their attributes. This study was conducted to inform people that each crop, depending on its requirements, can easily be directed towards a soil that suits its physico-chemical needs. This study examines the chemical and physical properties of soils across various regions of India, focusing on their agricultural production and environmental sustainability. The study was carried out in the year 2023-2024. Chemical testing revealed notable variations in soil pH and nutrient content. Phosphorus ran from 15 to 47 ppm; potassium from 180 to 270 ppm; nitrogen from 12 to 22 ppm; and pH from 5.4 to 6.8. Revealing the intricate interactions among several components improves correlation analysis and offers important information for the development of concentrated soil management strategies. The soil structure determines water retention capacity and nutrient availability regardless of loam, sand, or clayey. Studies of heavy metals revealed varying degrees of mercury, cadmium, arsenic, and lead all around India. Since it shows the changes in easily available water over time, the moisture content of the soil is vital for irrigation planning and agriculture. Emphasising the need for soil porosity (28.45% to 40.17%) and permeability (7.83 to 11.23 cm/hr) for water movement and root penetration is absolutely vital. These findings support informed decision-making in soil management, promoting sustainable agricultural practices tailored to regional soil characteristics. In conclusion, the comprehensive assessment of soil properties across diverse regions of India provides crucial insights for sustainable land management and agricultural practices. Future research should focus on long-term monitoring of soil health indicators and the impact of climate change on soil properties.